582 ANALYSIS OF FACTORS ASSOCIATED WITH CHANGE IN UES AND LES RESTING PRESSURE IN THE START AND END OF HRM STUDY. (14th September 2020) - Morozov, S; Kropochev, V; Bredenoord, A
Abstract:  : Lower and upper esophageal sphincter resting pressures' evaluation is not within Chicago classification, but is a part of a standard esophageal HRM examination. As the results of measurements at the beginning and at the end of examination are often discrepant, national guidelines in Russia recommend to record both. The aim of the study was to analyse possible factors that may affect the change between the results of the recordings of UES and LES resting pressures. Methods: High-resolution esopophageal manometry examinations were performed in upright position with solid-state 36 channel 10 Fr catheter (Unisensor, USA) and Solar (MMS, the Netherlands) equipment. Resting pressures (RP) were measured at rest for ≥30 seconds at the beginning of the examination and after 10 water swallows. Beck depression inventory (BDI-II) was used to assess psychological status. Correlation analysis by Spearman (StatSoft, USA) was used to reveal factors affecting the change in resting pressures at the beginning and at the end of HRM study. Change of pressure was presented as a quotient of dividing the second P value by the first (ΔP). Results: Eighty-four patients, age (M ± m) 48.5 ± 13.2 y.o. were enrolled. Hiatal hernia was present in 37 subjects. UES mean RP differed significantly at the beginning (123.7 ± 76.6 mmHg) and at the end of examination (87.9 ± 64.1), P < 0.0001. LES RP didn't differ significantly at the start and at the end of examination. The results of correlation analysis of factors affecting ΔP are shown in the table 1. Those with a decrease of UES resting pressure at the end of examination (n = 63) were younger compared to the group with no change or an increase of it (46.3 ± 12.7 y.o. vs 56.0 ± 13.1 y.o., p = 0.003). Conclusion: Upper esophageal resting pressure measured at the end of the high resolution esophageal examination is lower compared to the initial values in great proportion of patients. Despite the importance of the finding is unknown, this should be considered when the function of the upper esophageal sphincter is studied.